Consumer's Functional Values in Luxury Fashion Consumption: A Cross-cultural Comparison between Australia and China (Journal of Fiber Bioengineering and Informatics, 2023)
Consumers use functional values to evaluate fashion products, which are influenced by an individual's nationality and cultural background. Although previous cross-cultural studies in luxury consumption determined the similarities and differences between Western and Asian consumers, there is scarce information on the influence of functional value perception between Australian and Chinese millennial consumers in their luxury handbag purchasing. In this study, a consumer's functional values were measured through three specific values: usability, quality, and uniqueness. Usability value refers to an individual's evaluation of a handbag's functions as satisfying their needs, such as size and ease of use. Quality value is a consumer's evaluation of a handbag's physical qualities, such as material quality, craftsmanship, and lifespan. Uniqueness value is a consumer's need to be unique or distinct from others, which is evaluated in terms of a handbag's exclusivity. 49 Australian and 52 Chinese millennial luxury-fashion-brand consumers were invited to a survey that required participants to do a pairwise comparison of the importance of these three values on their purchasing decision of a luxury fashion handbag. This pairwise comparison method and data analysis were based on the analytic hierarchy process (AHP), which is a mathematically based, multi-objective, decision-making tool. The results demonstrate that quality value has the greatest impact on luxury fashion handbag purchasing decisions for both Australian and Chinese millennial consumers, while the uniqueness value has the lowest impact on former and the usability value on latter. This study may assist brands and product developers to better understand the influence of both Australian and Chinese consumers' functional values on their intention to purchase a luxury handbag from a cross-cultural perspective, helping to establish user-centered design criteria for developing luxury fashion handbags.
Keywords: Luxury Handbags; Accessories Design; Consumer Functional Values; Consumer Needs; Cross-cultural Study; Product development